2018
DOI: 10.1039/c8ra90032a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: β-Carotene: a natural osteogen to fabricate osteoinductive electrospun scaffolds

Abstract: Correction for ‘β-Carotene: a natural osteogen to fabricate osteoinductive electrospun scaffolds’ by Atiyeh Dabouian et al., RSC Adv., 2018, 8, 9941–9945.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their results showed that β-carotene embedded fibrous mats (polycaprolactone) were successfully providing a desirable environment for osteo-differentiation of seeded MSCs. 56 In this respect, based on the immunocytochemistry results of our study, the expression of SC-specific markers S100 and P75 ntr in ADSC/PDMS/β-carotene was elevated to roughly 84% and 75%, respectively. Moreover, q-real time PCR evaluations quantitatively confirmed their increase at a significant level (p-value<0.001).…”
Section: Immunocytochemistry Analysismentioning
confidence: 57%
“…Their results showed that β-carotene embedded fibrous mats (polycaprolactone) were successfully providing a desirable environment for osteo-differentiation of seeded MSCs. 56 In this respect, based on the immunocytochemistry results of our study, the expression of SC-specific markers S100 and P75 ntr in ADSC/PDMS/β-carotene was elevated to roughly 84% and 75%, respectively. Moreover, q-real time PCR evaluations quantitatively confirmed their increase at a significant level (p-value<0.001).…”
Section: Immunocytochemistry Analysismentioning
confidence: 57%